The Organization for Disaster in British Columbia - Larsen, A. A. (1962)
Plans are being formulated for organizing an Emergency Health Service in British Columbia. The same organization that is being created to deal with civilian casualties after an enemy attack should, it is felt, be able to assist in major natural disasters. Such an organization will have to remain ready but inactive for long periods; therefore the responsibility for planning, organizing and directing this service has been given to the Health Branch, Provincial Department of Health Services and Hospital Insurance. A committee has been struck to advise the Health Branch, and a Director and a Health Supplies Officer have been appointed. Agreement has been reached as to who is to be assigned to work in the Emergency Health Service in the event of a nuclear attack, and sites have been selected for the stockpiling of medical equipment. The Province has been divided into zones, and Emergency Health Service Directors have been appointed for each zone. Their duties include, among many others, organizing Advanced Treatment Centres and Emergency Hospitals, and developing an Emergency Public Health Service, an Emergency Blood Transfusion Laboratory and a Mortuary Service.